On the asymptotic representation of the solutions to the fourth general Painlevé equation. (27th February 2003) - Lu, Youmin
Abstract : There have been many results on the asymptotics of the Painlevé transcendents in recent years, but the asymptotics of the fourth Painlevé transcendent has not been studied much. In this note, we study the general fourth Painlevé equation and develop an asymptotic representation of a group of its solutions as the independent variable approaches infinity along a straight line.